Potential of Critical Mineral and Cytotoxicity Activity of Gadolinium Complex as Anti-amoebic Agent by Viability Studies and Flow Cytometry Techniques - Eny Kusrini; Fatimah Hashim; Azrina Aziz; Muhamad Fairus Noor Hassim; Anwar Usman; Lee D. Wilson; El-Sayed Negim; Agus Budi Prasetyo (AUIQ Complementary Biological System, 2024)
The screening of lanthanide as a critical mineral and used as an anti-amoebic agent is important to identify the safest method and mode of cell death to eliminate this microorganism from the host. In this study, gadolinium ion (Gd3+) that complexed with a short acyclic triethylene glycol (EO3) and in the presence of picric acid (HPic) as counter anion for anti-amoebic activity was explored. The trivalent Gd3+ complexed with EO3 and HPic via one-pot synthesis reaction using a mole ratio of gadolinium nitrate salt, EO3 ligand and HPic in a mole ratio 1:3:4 to produce [Gd(Pic)2(H2O)(EO3)]+(Pic)-.CH3OH. The viability of cells was assessed by using an MTT assay after 24 hours exposed to the Gd complex. The cytotoxicity of the Gd complex has an IC50 value of 23.44 µg/mL. The treated cells display orange organelles in the green cytoplasm after 24 h of incubation time and indicated that the cells experienced autophagic cell death. The externalisation of phosphatidylserine was not observed by flow cytometry techniques using Annexin V-FITC. Overall, the Gd complex is potent as anti-amoebic agent and is possible to use for the treatment of Acanthamoeba infection in future.